Design and Build JIG Design on Friction Stir Welding Using Fillet Connection on AA6061-T6 Material: Rancang Bangun Desain JIG pada Pengelasan Friction Stir Welding Menggunakan Sambungan Fillet pada Material AA6061-T6 - Soleh, Muhammad Zaenal Abidin; Mulyadi, Mulyadi (Universitas Muhammadiyah Sidoarjo, 2021)
This research was conducted to test the jig design that can be used in the Friction Stir Welding process on the fillet connection of two aluminum plates. The research method used is the experimental method in the engineering laboratory of the Muhammadiyah University of Sidoarjo. The jig design is a V shape for the aluminum plate base facing up so that the Friction Stir Welding welding is done vertically. The type of aluminum used is AA 6061-T6. The experimental results show that the jig can function well to support Friction Stir Welding at fillet joints using a chisel that has convex shoulders and a small degree of inclination. Jig design with three V plate supports can withstand tool pressure and provide stability during the welding process.Keywords – Jig, Friction Stir Welding, Aluminum